Analysis Of The Judge's Considerations In Granting Pre-Trial Applications Against Blocking Company Bank Account In Processinvestigation At Lampung Regional Police (Study of Decision Number 1/Pid.Pra/2025/PN Kla) - Bambang Hartono; Adek Suci Pebrianto (Cita konsultindo, 2026)
One of the cases related to pre-trial is Decision Number 1/Pid.Pra/2025/PN Kla. Decision Number 1/Pid.Pra/2025/PN Kla is an important reference in understanding the limits of the authority of law enforcement officers in carrying out coercive measures in the form of blocking accounts at the investigation stage. The research problem is how the judge's considerations in granting the pre-trial application for blocking a company's bank account during the investigation process at the Lampung Regional Police based on Decision Number 1/Pid.Pra/2025/PN Kla and What are the legal implications of Decision Number 1/Pid.Pra/2025/PN Kla which states that blocking a company's bank account at the investigation stage is invalid for the investigator's authority and the protection of the applicant's rights . The research method in this study is a normative juridical approach and an empirical approach and is concluded by deductive thinking so that it becomes a general picture of the answer to the problem based on the research results. The results of the study show that Decision Number 1/Pid.Pra/2025/PN Kla confirms that the cancellation of an investigation is not the object of a pretrial, but rather a consequence of declaring an investigation action invalid, such as a violation of human rights or the determination of an invalid suspect. In line with the Constitutional Court Decision No. 21/PUU-XII/2014, pretrial functions as a control mechanism against arbitrary actions by investigators, including searches, seizures, and investigations, to enforce the law and protect the rights of suspects. The implications of this decision indicate that blocking a company's bank account during an investigation is invalid if carried out without an adequate legal basis, thus providing protection for account ownership rights and the continuity of company operations. Suggestions for judges to emphasize the boundaries of the object of pretrial and distinguish between the cancellation of an investigation and actions that are the object of pretrial. Investigators need to understand the rights of suspects or defendants and legitimate legal procedures so that actions such as searches, seizures, and blocking of accounts do not give rise to legal disputes.